GOLD MINERS SOCIOECONOMIC CHANGE IN THE DISTRICT IV NAGARI KOTO TUO SIJUNJUNG DISTRICT OF WEST SUMATERA. THESIS. SOSIOLOGI OF EDUCATOIN STUDIES PROGRAM COLLEGE OF TEACHER TRAINING AND ADUCATION (STKIP PGRI) WEST SUMATERA PADANG.2014 - Alhamra, Bobi; Aziwarti, Aziwarti; Rahmad, Darmairal (Pendidikan Sosiologi, 2014)
Thesis examines the gold mining in Nagari Koto Tuo opportunities most people to change the standard of living for the better , giving the new changes in the lives of the people on the other negative impacts on the health hazards . The goal is achieved in this study was to describe : " Socioeconomic Change Gold Miners In Nagari Nagari Koto Tuo District IV District of Sijunjung " . The theory used is Neil Smelser s theory of social change . The approach used in this study is a qualitative approach , which approach intends to make a solid theoretical study . Informants research taken by purposive sampling . Informants in this study consisted of 16 persons , namely village trustees , community leaders , local communities and the people who work in the gold miners . This type of data is divided into words and actions. The words and the person who observed or interviewed the main source. Data collection techniques and tools used were interviews, observation , documentation and data collection tools such as interview guides,books,pens,andmobile phone. These results indicate that : Socioeconomic Change Gold Miners in the District IV Nagari Nagari Koto Tuo District Sijunjung a) . social change b ) . in increasing revenue , c ) . improve the education of children , d ) . increase employment e ) . improve existing facilities and infrastructure in society . f ) . income communities in addition to miners disrupted g ). patterns and peoples lifestyles .Â